Clinical trial of a digital scoliometer device for scoliosis diagnosis - Khalil A.; Nizar M.H.A.; Anis S.; Lai K.W. (Institute of Electrical and Electronics Engineers Inc., 2024)
Scoliosis is a complex three-dimensional deformity of the spine. The physicians usually examine the unevenness of the patients body to suspect scoliosis and conduct x-ray to confirm the severity of scoliosis. In case of severe scoliosis, a surgery will be considered. Few measurement indexes will be recorded pre-surgery and post-surgery. This measurement includes shoulder height difference (SHD), shoulder lateral tilting angle (SLTA), the angle of trunk rotation (ATR) and humps height difference (HHD). Although baseline scoliometer was utilized to measure these indexes, it is prone to parallax error and required additional spinal radiograph for HHD measurement. Thus, the aim of this research is to design and develop a digital scoliometer that can measure HHD along with SHD, SLTA, and ATR. This stable portable device could avoid human errors during examination and also reduce the harmful effect of x-ray to diagnose and measure the severity of scoliosis. A Printed Circuit Board (PCB) was also developed to make the device more compact and to reduce the risk of data loss. Clinical testing on 17 candidates was conducted to test the accuracy of the prototype and the results obtained show high similarity with gold standards measurement from the baseline scoliometer. 2018 IEEE